Pemberdayaan Difabel dalam Wirausaha melalui Model LSM untuk Daya Saing Inklusif - Uli Wildan Alfiyah Nuryanto; Dewi Robiatun Muharomah; Ririn Nur Abdiah Bahar; Basrowi Basrowi; Eva Mutiah (GUYUB: Journal of Community Engagement, 2024)
Community service at the Disabled Foundation aims to improve the skills, knowledge and independence of people with disabilities through methods of learning simulation and mentoring. This program is designed to provide interactive, simulation-based training that allows participants to learn practical skills and relevant knowledge in an applicable way. This simulation adapts real-world situations so that participants can practice and understand the skills needed in everyday life and the work environment. Apart from that, this program also provides personal support through methods of mentoring, which connects participants with experienced mentors. Mentors will provide guidance, motivation and emotional support to help participants overcome personal and professional challenges and achieve their goals. With this guidance, it is hoped that participants can increase their self-confidence and achieve better independence. The main goal of this program is to strengthen the connectedness and involvement of people with disabilities in the community. By involving people with disabilities in training simulations and providing access to mentors who understand their needs, this program aims to increase the sense of inclusion and social participation among people with disabilities, as well as improve the quality of life disabled people overall. It is hoped that this program can become an effective model for skill development and community support for people with disabilities in the future.